Avaliação da fosforilação da AKT e do conteúdo da proteína transportadora de glicose GLUT4 em tecido muscular esquelético de ratos adultos, proles de ratas com doença periodontal - Mattera, Maria Sara de Lima Coutinho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The fetal programming hypothesis suggests that intrauterine stimuli or aggression can induce metabolic and physiology changes in offspring, increasing the diseases risk in adulthood. Studies have demonstrated that periodontal disease (PD) and adipose tissue augmentation enhance the cytokines levels. Cytokines such as TNF-α have been associated with reduced GLUT4 expression and insulin resistance. Knowing that GLUT4 is important for glucose homeostasis, the aim of present study was to evaluate in adult rats, offspring of rats with periodontal disease: 1) birth weight and during the 75 days of age; 2) GLUT4 content and its translocation index in gastrocnemius skeletal muscle tissue (GM); 3) Akt serine phosphorylation status in MG. Female Wistar rats were distributed into a control group (CN, n = 4) and a experimental periodontal disease group (PD, n = 4), in which the disease is induced by ligation with silk thread around the 1st molar. Seven days after ligature placement, animals from both groups mated and daily vaginal smears were taken to verify the presence of sperm. Pregnant rats were kept in individual cages. The body weights of the offspring were measured once weekly from birth until 75 days of age. When male offspring of these rats completed 75 days, the experiments were performed: 1) assessment of plasma concentrations of glucose and insulin; 2) evaluation of the GLUT4 content and its translocation index in GM; 3) Akt serine phosphorylation status in GM. The results showed that maternal periodontal disease causes in their offspring low birth weight, and in adulthood: 1) no changes in glycemia; 2) increase in insulinemia; 3) insulin resistance; 4) decrease in GLUT4 content in the plasma membrane and its translocation index in GM; 5) reduction in the Akt serine phosphorylation status in GM. Therefore, we can conclude that maternal periodontal disease causes...

A hipótese da programação fetal sugere que estímulos ou agressões durante a vida intrauterina podem resultar em alterações permanentes na fisiologia e metabolismo da descendência, aumentando o risco de doenças na vida adulta. Estudos demonstraram que tanto a doença periodontal (DP) como o aumento do tecido adiposo elevam a concentração plasmáticas de citocinas. E citocinas, como por exemplo, o TNF-, têm sido relacionadas com a redução da expressão de GLUT4 e resistência à insulina. Sabendo que o GLUT4 é importante para homeostase glicídica, o objetivo do presente estudo foi avaliar em ratos, proles de ratas com doença periodontal ao nascimento, a massa corpórea, e na vida adulta: 1) massa corpórea ao longo de 75 dias de idade; 2) o conteúdo da proteína transportadora de glicose GLUT4 e o seu índice de translocação em tecido muscular esquelético gastrocnêmio (MG); 3) o grau de fosforilação em serina da Akt em MG. As ratas foram distribuidas em dois grupos: a) com doença periodontal (DP), no qual esta doença foi induzida por meio de ligadura com fio de seda ao redor do 1º molar inferior de ambos os lados; b) ratas controle (CN). Após 7 dias da colocação da ligadura, as ratas de ambos os grupos foram colocadas para acasalamento, verificou-se diariamente, por esfregaço vaginal, o dia da copulação. As ratas prenhas foram separadas em caixas individuais. A massa corpórea da prole foi avaliada ao nascimento e durante os 75 dias de idade. Quando os filhotes machos destas ratas completaram 75 dias, realizou-se: 1) dosagem de glicemia e insulinemia; 2) avaliação da proteína transportadora de glicose GLUT4 e seu índice de translocação em MG; 3) avaliação do grau de fosforilação em serina da Akt em MG. Os resultados demonstraram que a doença periodontal materna promove em sua prole ao nascimento baixo peso e na vida adulta...
Keywords: Doenças periodontais; Resistência à insulina; Diabetes Mellitus Tipo 2; Inflamação